Budaya dan Etika Pelayanan Publik: Nilai, Norma, dan Tantangan dalam Administrasi Publik - Sri Yulianty Mozin; Siti Mardia Mareteng; Fadila Ladiku; Rahmawaty M. Noho; Cipta Monoarfa (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This research is motivated by the importance of strengthening a professional public service culture through the integration of public administration values, norms, and ethics. Although various regulations and codes of ethics have been established in public organizations, gaps remain between formal norms and service practices in the field, such as low levels of responsiveness and professionalism among civil servants. This study aims to analyze the relationship between values, norms, and ethics in shaping public service culture, and to examine the role of organizational ethics and codes of ethics in strengthening public administration professionalism. The research employed a qualitative approach with a descriptive-analytical design through a literature review of relevant journals, books, and policy documents. Content analysis techniques were used to identify patterns of relationships between concepts. The results indicate that the internalization of ethical values ​​such as integrity, accountability, and transparency significantly influences the quality of public services. An organizational code of ethics serves as a formal instrument that clarifies standards of conduct for civil servants and strengthens a professional work culture. Consequently, public organizations need to strengthen ethics training, oversight mechanisms, and the integration of ethical values ​​into performance evaluation systems to build responsive and public-interest-oriented services.